Profil Critical Thinking Awareness Siswa pada Siswa Kelas X di Pembelajaran Fisika - Muhammad Hoerul Umam; Siti Nurdianti Muhajir; Amar Amrullah (Universitas Garut, 2026)
Critical thinking skill is frequently the primary focus of physics education research, while its underlying foundation, critical thinking awareness, remains rarely examined, particularly among Senior High School students. This study aims to describe the profile of students' critical thinking awareness in physics learning, identify the most influential indicator, and examine differences based on gender. A quantitative descriptive method was employed involving 30 tenth-grade students (10 males and 20 females) at a Madrasah Aliyah in Garut Regency as respondents. Data were collected using a closed five-point Likert questionnaire measuring three indicators: beliefs and appreciation of logic, metacognitive caution, and academic self-efficacy. The instrument was valid (r = 0.69-0.87) and reliable (Cronbach's Alpha = 0.963). Results showed that students' mean critical thinking awareness score was 50.80 out of a maximum of 75 (67.7%), classified as moderate-to-high, with a relatively balanced profile across the three indicators (range 3.36-3.42). An independent samples t-test revealed a significant gender difference (t = -2.86; p = 0.008), with female students (M = 54.05) demonstrating higher critical thinking awareness than male students (M = 44.30), accompanied by a large effect size (Cohen's d = 1.11). These findings emphasize the need for physics teachers to design instructional strategies that build metacognitive awareness as a foundation prior to training higher-order critical thinking skills, while also attending to the gender gap in students' thinking dispositions.Keywords: critical thinking awareness, gender, metacognitive awareness, physics learning